The rs8506 TT Genotype in lincRNA-NR_024015 Contributes to the Risk of Sepsis in a Southern Chinese Child Population - Li, Jinqing; Zhou, Huazhong; Wei, Bing; Che, Di; Xu, Yufen; Pi, Lei; Fu, Lanyan; Hong, Jie; Gu, Xiaoqiong (Frontiers in Public Health, 2022)
Background: Sepsis is a highly life-threatening heterogeneous syndrome and a global health burden. Studies have shown that many genetic variants could influence the risk of sepsis. Long non-coding RNA lincRNA-NR_024015 may participate in functional alteration of endothelial cell via vascular endothelial growth factor (VEGF) signaling, whereas its relevance between the lincRNA-NR_024015 polymorphism and sepsis susceptibility is still unclear. Methods: 474 sepsis patients and 678 healthy controls were enrolled from a southern Chinese child population in the present study. The polymorphism of rs8506 in lincRNA-NR_024015 was determined using Taqman methodology. Results: Overall, a significant association was found between rs8506 polymorphism and the risk of sepsis disease (TT vs. CC/CT: adjusted OR = 1.751, 95%CI = 1.024–2.993, P = 0.0406). In the stratified analysis, the results suggested that the carriers of TT genotypes had a significantly increased sepsis risk among the children aged 12–60 months, females, early-stage sepsis and survivors (TT vs. CC/CT: ORage = 2.413; ORfemale = 2.868; ORsepsis = 2.533; ORsurvivor = 1.822; adjusted for age and gender, P < 0.05, respectively). Conclusion: Our study indicated that lincRNA-NR_024015 rs8506 TT genotype might contribute to the risk of sepsis in a southern Chinese child population. Future research is required to elucidate the possible immunoregulatory mechanisms of this association and advance the development of novel biomarkers in sepsis.